Raising concerns about the Sepsis-3 definitions - Sartelli, Massimo; Kluger, Yoram; Ansaloni, Luca; Hardcastle, Timothy C; Rello, Jordi; Watkins, Richard R; Bassetti, Matteo; Giamarellou, Eleni; Coccolini, Federico; Abu-Zidan, Fikri M; Adesunkanmi, Abdulrashid K; Augustin, Goran; et al. (World journal of emergency surgery, 2018)
The Global Alliance for Infections in Surgery appreciates the great effort of the task force who derived and validated the Sepsis-3 definitions and considers the new definitions an important step forward in the evolution of our understanding of sepsis. Nevertheless, more than a year after their publication, we have a few concerns regarding the use of the Sepsis-3 definitions.
Keywords: stupeň závažnosti nemoci; Sepsis; arteriální tlak; Consensus; konsensus; Septic shock; Sensitivity and Specificity; Organ dysfunction; Organ Dysfunction Scores; Data Accuracy; Glasgowská stupnice kómat; Humans; vyhodnocení orgánové dysfunkce; Infections; sepse; Arterial Pressure; senzitivita a specificita; Glasgow Coma Scale; správnost dat; Severity of Illness Index; lidé